AyudaMujer: A Mobile Application for the Treatment of Violence Against Women in Peru - Mauricio, David (2024)
Violence against women in Peru is a problem that has a high incidence and is increasing, despite the policies undertaken by past governments and the creation of the Ministry of Women and Vulnerable Populations in 1996, causing that one in two women have been abused at some point in their lives. However, the treatment of abused women is still insufficient even though there are more Women’s Emergency Centers (WEC) each year, where victims can ask for professional support and treatment quickly and effectively. The chatbot provides an alternative to eliminate the distance between the abused woman and the WEC; therefore, a mobile application called AyudaMujer is proposed that includes a chatbot, news, a map of nearby WECs, and the connection with specialists for the treatment of violence against women. The chatbot identifies, automatically and through a natural dialogue, the type of violence and its level of risk. Additionally, it assigns a specialist to provide personalized professional treatment. The testing of AyudaMujer with 20 abused women from Lima, Peru, shows that the risk of violence is reduced by an average of 19.43% after three weeks of use. The results show that this tool can contribute to the treatment of abused women.